Sexual segregation and abundance trend of whale sharks in southern Mozambique - Auditore, Lisa-Marie (Department of Biological Sciences, 2023)
Coastal aggregations of endangered whale sharks (Rhincodon typus) consist mainly of juveniles, and most have a strong male bias. Generalised additive models were constructed on a 15-year dataset (2005–2019), from Praia do Tofo, Mozambique, to investigate sexual segregation in relation to environmental conditions. Temporal (year, day of year), and biophysical (sea surface temperature, time from high tide, moon illumination, Indian Ocean dipole index, wind, and chlorophyll a concentration) predictors were modelled in relation to the total, male, and female sightings. Encounter histories of individual sharks were then used in three capture-markrecapture model parameterisations to test for sex-specific demographic variables, and evaluate trends within the constellation. No differences in selected environmental variables were found between males and females, and demographic parameters were similar. Segregation does not occur from a preference for localised habitat conditions; while fewer females are present, they make use of the area similarly to males. Declining annual sighting trends corroborate trends in the seasonal abundance from multi-state open robust design models. Total abundance decreased over the study period (89%), with females (92%) declining at a greater rate than males (81%) suggesting exposure to different conditions or threats. The rapid decline indicates a need for a detailed threat assessment to assess potential causes.